Psychological, Cardiometabolic, and Musculoskeletal Morbidity and Multimorbidity Among Adults With Cerebral Palsy and Spina Bifida: A Retrospective Cross-sectional Study. (18th October 2021) - Peterson, Mark D.; Lin, Paul; Kamdar, Neil; Hurvitz, Edward A.; Mahmoudi, Elham
Abstract : Supplemental digital content is available in the text. Abstract : Background: Individuals living with cerebral palsy or spina bifida are at heightened risk for a number of chronic health conditions, such as secondary comorbidities, that may develop or be influenced by the disability, the presence of impairment, and/or the process of aging. However, very little is known about the prevalence and/or risk of developing secondary comorbidities among individuals living with cerebral palsy or spina bifida throughout adulthood. The objective of this study was to compare the prevalence of psychological, cardiometabolic, and musculoskeletal morbidity and multimorbidity among adults with and without cerebral palsy or spina bifida. Methods: Privately insured beneficiaries were included if they had an International Classification of Diseases, Ninth Revision, Clinical Modification diagnostic code for cerebral palsy or spina bifida ( n = 29, 841). Adults without cerebral palsy or spina bifida were also included ( n = 5, 384, 849). Prevalence estimates of common psychological, cardiometabolic, and musculoskeletal morbidity and multimorbidity (≥2 conditions) were compared. Results: Adults living with cerebral palsy or spina bifida had a higher prevalence of all psychological disorders and psychological multimorbidity (14.6% vs. 5.4%), all cardiometabolic disorders and cardiometabolic multimorbidity (22.4% vs. 15.0%), and all musculoskeletal disorders and musculoskeletal multimorbidity (12.2% vs. 5.4%), as compared with adults without cerebral palsy or spina bifida, and differences were to a clinically meaningful extent. Conclusions: Adults with cerebral palsy or spina bifida have a significantly higher prevalence of common psychological, cardiometabolic, and musculoskeletal morbidity and multimorbidity, as compared with adults without cerebral palsy or spina bifida. Efforts are needed to facilitate the development of improved clinical screening algorithms and early interventions to reduce risk of disease onset/progression in these higher risk populations. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) List the main categories of morbidity that present with higher risk in adults with cerebral palsy and spina bifida; (2) Discuss the potential impact of multimorbidity on 'early aging' in adults living with cerebral palsy and spina bifida; and (3) Describe challenges that adults with cerebral palsy and spina bifida have in obtaining appropriate health care to address prevention and treatment of multimorbidity. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity.